Ventilatory chemosensory drive is blunted in the mdx mouse model of Duchenne Muscular Dystrophy (DMD) - Mosqueira, Matias; Baby, Santhosh M.; Lahiri, Sukhamay; Khurana, Tejvir S. (PLOS ONE, 2013)
Duchenne Muscular Dystrophy (DMD) is caused by mutations in the DMD gene resulting in an absence of dystrophin in neurons and muscle. Respiratory failure is the most common cause of mortality and previous studies have largely concentrated on diaphragmatic muscle necrosis and respiratory failure component. Here, we investigated the integrity of respiratory control mechanisms in the mdx mouse model of DMD. Whole body plethysmograph in parallel with phrenic nerve activity recordings revealed a lower respiratory rate and minute ventilation during normoxia and a blunting of the hypoxic ventilatory reflex in response to mild levels of hypoxia together with a poor performance on a hypoxic stress test in mdx mice. Arterial blood gas analysis revealed low PaO2 and pH and high PaCO2 in mdx mice. To investigate chemosensory respiratory drive, we analyzed the carotid body by molecular and functional means. Dystrophin mRNA and protein was expressed in normal mice carotid bodies however, they are absent in mdx mice. Functional analysis revealed abnormalities in Dejours test and the early component of the hypercapnic ventilatory reflex in mdx mice. Together, these results demonstrate a malfunction in the peripheral chemosensory drive that would be predicted to contribute to the respiratory failure in mdx mice. These data suggest that investigating and monitoring peripheral chemosensory drive function may be useful for improving the management of DMD patients with respiratory failure.
Gesehen am 09.06.2021